2007
DOI: 10.1111/j.1349-7006.2007.00441.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein expression associated with early intrahepatic recurrence of hepatocellular carcinoma after curative surgery

Abstract: The poor prognosis of patients with hepatocellular carcinoma (HCC) is attributed to intrahepatic recurrence. To understand the molecular background of early intrahepatic recurrence, we conducted a global protein expression study. We compared the protein expression profiles of the primary HCC tissues of 12 patients who showed intrahepatic recurrence within 6 months post surgery with those of 15 patients who had no recurrence 2 years post surgery. Two-dimensional difference gel electrophoresis identified 23 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Previous studies have reported the upregulation of PDIA3 protein and mRNA levels in HCC (7,10), which is consistent with the results of the current study. However, in previous proteomic studies, PDIA3 was not identified as a candidate biomarker indicating early recurrence and metastasis of HCC (9,11). This may be partially due to patient selection as these studies were conducted with patients in which recurrence and metastasis occurred within 6 months of the treatment, while only 15% of patients in the current study experienced recurrence and metastasis within this same time frame.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies have reported the upregulation of PDIA3 protein and mRNA levels in HCC (7,10), which is consistent with the results of the current study. However, in previous proteomic studies, PDIA3 was not identified as a candidate biomarker indicating early recurrence and metastasis of HCC (9,11). This may be partially due to patient selection as these studies were conducted with patients in which recurrence and metastasis occurred within 6 months of the treatment, while only 15% of patients in the current study experienced recurrence and metastasis within this same time frame.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have performed proteomic analyses of HCC (711) and identified candidate proteins for the early diagnosis (7,10) and rapid progression of HCC (9,11). However, only a limited number of patients were examined in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…( 11 ) which applied DNA microarray technology to HCC research for the first time. Thereafter, various class prediction studies, ( 25–31,58,59 ) using DNA microarray or other technologies have been performed (Table 1). Many studies ( 25–27,30,31,58,59 ) have used primary HCC tissues in the search for predictive gene signatures, although two DNA microarray studies used non‐cancerous liver tissues to predict the occurrence of de novo HCC, ( 28 ) and recurrence.…”
Section: Class Prediction Studiesmentioning
confidence: 99%
“…Thereafter, various class prediction studies, ( 25–31,58,59 ) using DNA microarray or other technologies have been performed (Table 1). Many studies ( 25–27,30,31,58,59 ) have used primary HCC tissues in the search for predictive gene signatures, although two DNA microarray studies used non‐cancerous liver tissues to predict the occurrence of de novo HCC, ( 28 ) and recurrence. ( 29 ) Among nine studies, ( 25–31,58,59 ) four used oligonucleotide arrays, four used cDNA arrays, and one used polymerase chain reaction (PCR)‐based array.…”
Section: Class Prediction Studiesmentioning
confidence: 99%
“…By monitoring pfetin expression, we may be able to select the patients who may have optimal benefits from adjuvant therapy with imatinib. In liver cancer proteomics, we detected the expression patterns of 23 proteins corresponding to the early intrahepatic recurrence of hepatocellular carcinoma (HCC) after curative surgery (14). Moreover, by focusing on the histological differentiation, we identified APC-binding protein EB1 (EB1) as a novel prognostic biomarker for patients with HCC (15).…”
Section: Tissue Proteomics For Biomarker Development For Personalizedmentioning
confidence: 99%